City energy audit based on research template MDN/R+E as the instrument of planning energy saving measures at urban level - Anna Ostańska; Katarzyna Taracha (Budownictwo i Architektura, 2011)
The aim of the research project was to develop a City Energy Audit (CEA) for Lublin, Poland. CEA collects information on the built environment and city infrastructure in a systematic way, and provides structural analyses with special focus on housing stock. The purpose of CEA is to provide reliable input for analysing current and future energy consumption patterns, i.e. the basis for planning effective and viable energy saving measures at urban level. The CEA’s fitness for purpose was confirmed in practice – it was used by the local authorities in the process of preparing the Study of the conditions and directions of spatial planning for the City of Lublin in September 2011. To present the idea of applying CEA, the authors use their original template of Possible Retrofit/Repair and Energy Saving Measures (further referred to as MDN/R+E) and develop it into detailed solutions using the example of an 11-storey prefabricated block of flats.